Perbandingan komplikasi antara fakoemulsifikasi dan manual Small-Incision Cataract Surgery (mSICS) pada operasi katarak massal: Sebuah penelitian kohort retrospektif - Tri Winarti; Indra Tri Mahayana; Reny Setyowati; Suhardjo Pawiroranu (Journal of Community Empowerment for Health, 2019)
Cataract is the most common cause of reversible blindness, and its prevalence have been increasing in the community depend on the age. Phacoemulsification and manual Small-Incision Cataract Surgery (mSICS) were the techniques of cataract surgery that was frequently used in high-volume cataract surgery setting. This study aimed to compare the complications between phacoemulsification and mSICS in high-volume cataract surgery. This research was a retrospective cohort study with the data taken from the medical record of high-volume cataract surgery organized by Community Ophthalmology Division, Department of Ophthalmology Universitas Gadjah Mada (UGM) from January 2018 to November 2018. Cataract surgery was performed by consultant ophthalmologists, general ophthalmologist, and senior ophthalmology resident for phacoemulsification and by senior ophthalmology resident and junior ophthalmology resident for mSICS. Intraoperative and postoperative complications (i.e. posterior capsule rupture, vitreous prolapse, aphakia, iridodialysis, endophthalmitis) until four weeks of follow up were compared in both techniques. There were 483 patients who had been operated, 188 (38.9%) patients underwent phacoemulsification and 295 (61.1%) patients underwent mSICS. Intraoperative and postoperative complications in phacoemulsification and mSICS performed by senior ophthalmology resident were no statistically significant different (p > 0.05). Nevertheles, there was statistically significant different in the complication of posterior capsule rupture and aphakia in phacoemulsification based on the level of surgeon’s skill (p < 0.05). Most of them performed by senior ophthalmology resident in 11 (35.5%) cases and 5 (16.1%) cases respectively. However, complications in mSICS were no significantly different based on the level of surgeon’s skill performed by senior ophthalmology resident and junior ophthalmology resident (p > 0.05). Complications in phacoemulsification and mSICS performed by senior ophthalmology resident with relatively similar in the level of surgeon’s skill were not significantly different. However, the complication of posterior capsule rupture and aphakia in phacoemulsification was significantly different based on the level of surgeon’s skill.